Riding the wave of the emerging surf market: business plan for the implementation of the surf accessories brand “Escudo” - Geisler, Katia (2019)
The objective of this master thesis is the elaboration of a viable Business Plan for the surfboard cover brand ESCUDO. This business plan studies the viability of the creation of a company competing in the surf accessories industry in Portugal, producing sustainable, high-quality surfboard covers made out of ocean waste. In order to develop the business plan, the methodology of strategic business planning1 is used with the sub steps containing 1. Conducting strategic business review 2. Business visioning 3. Business strategy development 4. Implementation formulation Primary and secondary sources are used to gather insights about the surf industry as well as customer behavior in the target region before creating the business plan. Quantitative and qualitative research was conducted in the form of questionnaires, addressing the surfing community as well as expert interviews to gather deeper insights and expert knowledge from the surf industry. This plan aims to serve the foundress as a guide for the implementation of the venture as it plays an important role in a company’s well-being due to its high impact on profitability, stability and finding the most suitable position for the business in the market. The analysis reveals a gap in the surfboard cover market and the research results as well as the thorough market study clearly indicate that the creation of the surfboard cover brand ESCUDO can result in a lucrative business idea to pursue. The plan contains in detail all relevant intermediate steps needed to be undertaken in order to enter the market with this innovative product.